PESAN DAKWAH MELALUI APLIKASI TIKTOK PADA AKUN @KADAMSIDIK00 (ANALISIS SEMIOTIKA ROLAND BARTHES) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study aims to analyze the da'wah messages, language style, and packaging techniques in the three most popular videos of the TikTok account @kadamsidik00 owned by Husain Basyaiban, using a descriptive qualitative approach and Roland Barthes' semiotic theory. The results of the study show that the da'wah messages conveyed include the themes of Akidah, Akhlak, and Sharia, packaged in relaxed, contemporary language, and simple visuals that are easy to understand and relevant to the younger generation. The delivery techniques used include short duration, no background music, light delivery style, and minimalist editing. The implications of this study indicate that social media such as TikTok can be an effective and flexible means of da'wah in reaching society in the digital era.